2016
DOI: 10.5539/ies.v9n6p53
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Optimism, Religiosity and Self-Esteem with Marital Satisfaction and Life Satisfaction

Abstract: Domestic violence against females is a very common issue In any culture, religion and ethnicity and several reasons are found to be related with it which probably cause serious health outcomes. The study was undertaken to examine the perceived stress, life satisfaction and self-esteem among females facing domestic violence. It was a correlation research study being conducted in three different centers i.e. Dar-ul-Amaan, Dastak Shelter Homes and Shaheed Benazir Bhutto Human Rights Centre for Women, Lahore Pakis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
1
8
0
2
Order By: Relevance
“…The results of the present study demonstrated that various factors play a role in creating marriage life satisfaction among infertile couples so that paying attention to them can play an important role in facilitating good mental well-being concerning marriage. The findings of the present study support various previous findings in the literature (Cann and Collette 2014;Ghadami and Khalatbari 2015;Gorman and Jordan 2015;Homaei et al 2016). The results indicated the importance of attention to the psychological health of infertile couples.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of the present study demonstrated that various factors play a role in creating marriage life satisfaction among infertile couples so that paying attention to them can play an important role in facilitating good mental well-being concerning marriage. The findings of the present study support various previous findings in the literature (Cann and Collette 2014;Ghadami and Khalatbari 2015;Gorman and Jordan 2015;Homaei et al 2016). The results indicated the importance of attention to the psychological health of infertile couples.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies in the field of well-being have confirmed that optimistic people experience more marital satisfaction (Homaei et al 2016). Psychological theories and studies concerning life satisfaction have conceptualized optimism with life satisfaction and the expectation of a better future (Mirahmadi 2009) and can be a predictor of a couple's marital quality (Homaei et al 2016;Smith et al 2013b). Findings from earlier studies on couples' understanding of life show that positive traits such as optimism have an important effect on long-term marital satisfaction among couples (Ko et al 2007;Turliuc and Candel 2017), and enhance intimacy (Sabouripour and Roslan 2015).…”
Section: Optimism Marital Satisfaction Positive Affect and Negativmentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, optimism was predictive of life satisfaction of middle-aged women and community-dwelling older adults (Daukantaitė & Zukauskiene, 2012; Dumitrache, Windle, & Herrera, 2015). In addition, optimism was associated with life satisfaction of secondary school students, adolescents, college students and married university students (Homaei, Bozorgi, Ghahfarokhi, & Hosseinpour, 2016; Kapikiran, 2012; Santilli, Marcionetti, Rochat, Rossier, & Nota, 2017; Wong & Lim, 2009).…”
Section: Introductionmentioning
confidence: 99%